Roles of the recJ and recN Genes in Homologous Recombination and DNA Repair Pathways of Neisseria gonorrhoeae - Skaar, Eric P. (American Society for Microbiology, 2002)
The paradigm of homologous recombination comes from Escherichia coli, where the genes involved have been segregated into pathways. In the human pathogen Neisseria gonorrhoeae (the gonococcus), the pathways of homologous recombination are being delineated. To investigate the roles of the gonococcal recN and recJ genes in the recombination-based processes of the gonococcus, these genes were inactivated in the N. gonorrhoeae strain FA1090. We report that both recN and recJ loss-of-function mutants show decreased DNA repair ability. In addition, the recJ mutant was decreased in pilus-dependent colony morphology variation frequency but not DNA transformation efficiency, while the recN mutant was decreased in DNA transformation efficiency but not pilus-dependent variation frequency. We were able to complement all of these deficiencies by supplying an ectopic functional copy of either recJ or recN at an irrelevant locus. These results describe the role of recJ and recN in the recombination-dependent processes of the gonococcus and further define the pathways of homologous recombination in this organism.